Pengembangan Sistem Informasi Posyandu Balita Bintang Timur Pada RW 17 Kelurahan Sendangmulyo Kota Semarang - Werdhiningsih, Alana Sharfina; Februariyanti, Herny (MEANS (Media Informasi Analisa dan Sistem), 2024)
Posyandu is a primary healthcare service that plays an essential role in monitoring child growth and maternal health in communities. However, manual record-keeping still used by “Bintang Timur” Posyandu in RW 17, Sendangmulyo Subdistrict, Semarang City, has led to delays in data processing and reporting. This study aims to design and develop a web-based information system to enhance the efficiency and accuracy of Posyandu data management. The system was deveIoped using the WaterfaIl model and built with PHP, Laravel, and MySQL technologies. The results show that the system effectively manages child data, visit records, immunizations, and generates digital reports. The implementation of this system accelerates data entry, minimizes errors, and facilitates easier access to information for cadres and related parties. Therefore, the system is expected to support more effective, transparent, and sustainable healthcare services.